Influence of structure on the electrooxidation rate of six C-4 alcohols. (10th January 2022) - Ureta-Zañartu, María Soledad; Ilabaca, Jacqueline; Mascayano, Carolina
Highlights: The influence of the structure of butanol on its oxidation on a gold electrode in an alkaline medium was studied. The boiling temperature is a good descriptor for the oxidation of butanols on gold electrode in alkaline medium. Butanols with unsaturation in the carbon chain are more active than those without carbon-carbon double bond. The gold electrode surface is more active if the active site has been newly regenerated. Abstract: Alcohols are of great interest both for fuel cells and for the preparation of aldehydes. The electrooxidation of six C-4 alcohols (1-, 2- and iso-butanol, crotyl, cis-2-buten-1, 4-diol and erythritol on gold in alkaline medium has been studied by cyclic voltammetry (CV), the Electrochemical Quartz Crystal Microbalance (EQCM) and Electrochemical Impedance Spectroscopy (EIS). Furthermore, molecular dynamics calculations were used for determining the probability of solvation of the alcoholic head, g(r), as a function of the distance, r, to the alcoholic head. This probability was found to be maximum at r = 2 Å The six alcohols fell into two groups. One group, namely 1-, 2- and iso-butanol, showed first-order electrooxidation kinetics at concentrations <20 mM, without poisoning of the electrode surface. These alcohols, as well as including crotyl, showed relative low reactivity (It was estimated as the ratio of the charge of peak b1 in a given alcohol to that of iso-butanol, the less active alcohol) correlation against the Radial Distribution Function (RDF) at a given distance (g(2 Å)), in total agreement with our hypothesis about the effect of the hydrophobicity of the analyte on the reactivity of the electrode. The second group, formed by crotyl, cis-2-buten-1, 4-diol and erythritol, were almost 10 times more reactive, had a kinetic order near 0.5, showed adsorption on the gold surface, and their activity correlated better with their boiling points, that is, with their dipolar character. So, in the electrooxidation of unsaturated alcohols there is adsorption of residues and/or reaction products, which does not affect their high reactivity. Graphical abstract: Image, graphical abstract